Biochemistry and molecular biology (Oxford University Press, 2014)
Now in its fifth edition, Biochemistry and Molecular Biology features a new author team, who have retained the much-praised clarity of previous editions, while adding a greater focus on biomedical issues and incorporating a discussion of recent developments in research. A new chapter on the general principles of nutrition emphasizes the key principles underlying complex metabolic pathways, enabling students to appreciate an integrated view of human metabolism and nutrition. The fifth edition also features a new chapter on the control of gene expression reflects our increasing understanding of the importance and power of gene regulation.